A Nuclear Zip Code in SKS1 mRNA Promotes Its Slow Export, Nuclear Retention, and Degradation by the Nuclear Exosome/DRN in Saccharomyces cerevisiae. Issue 19 (6th September 2019) - Das, Subhadeep; Biswas, Subir; Chaudhuri, Shouvik; Bhattacharyya, Arindam; Das, Biswadip
Abstract: In Saccharomyces cerevisiae, a special class of mRNAs representing a subset of otherwise normal transcripts displays very slow export and an unusually long intra-nuclear dwell time. This prolonged nuclear retention leads to their rapid degradation in the nucleus by the nuclear exosome and DRN ( D ecay of R NA in the N ucleus) apparatus. We previously attributed their slow export to one or more hypothetical cis -acting, export-retarding element(s). Here, we identified such a cis -element (hereafter referred to as "nuclear zip code") in SKS1 mRNA, a representative of this class of transcripts. Deletion analysis of SKS1 mRNA identified a 202-nt RNA segment within the SKS1 ORF, which harbors the nuclear zip code. Removal of this segment (i) abolished slow export of the transcripts, as revealed by in situ confocal microscopy-based localization experiments, and (ii) abrogated the susceptibility of the transcripts to degradation by the nuclear exosome/DRN. Remarkably, fusing the SKS1 mRNA 202-nt nuclear zip code to the 5′-segment of CYC1 mRNA resulted in inefficient export, and susceptibility of the chimeric transcript to the nuclear exosome/DRN. These findings identify a cis -acting zip code element that is necessary and sufficient to impede nuclear export and results in its preferential nuclear retention, thereby impacting its abundance and cellular repertoire. We conclude that this element posttranscriptionally regulates SKS1 gene expression levels. Graphical abstract: Unlabelled Image